25-Hydroxyvitamin D Concentrations and Clostridium difficile Infection: A Meta-Analysis. (July 2017) - Furuya-Kanamori, Luis; Wangdi, Kinley; Yakob, Laith; McKenzie, Samantha J.; Doi, Suhail A. R.; Clark, Justin; Paterson, David L.; Riley, Thomas V.; Clements, Archie C. A.
Background: Well-known risk factors for Clostridium difficile infection (CDI) are exposure to antibiotics and gastric acid suppressants. Recent studies have provided some evidence of an association between hypovitaminosis D and the risk of CDI. Therefore, this meta-analysis aimed to pool all the existing evidence to investigate the association between 25-hydroxyvitamin D (25[OH]D) and CDI. Methods : A systematic search was conducted in 3 databases (PubMed, Embase, and Web of Sciences) for epidemiological studies that examined the association between mean 25(OH)D concentrations and CDI as well as between 25(OH)D status and CDI severity or recurrence. 25(OH)D status was defined as "lower" or "higher" at a threshold concentration of <20 or ≥20 ng/mL, respectively. Pooled effect sizes were computed using the inverse variance heterogeneity model of meta-analysis. Results : Eight publications (n = 4479 patients) were included in the meta-analysis. The mean concentration of 25(OH)D in patients with CDI was 3.54 ng/mL (95% confidence interval [CI], 0.39–6.89 ng/mL) lower than in patients without CDI. Patients with lower 25(OH)D status had a higher odds (odds ratio [OR], 1.61; 95% CI, 1.02–2.53) of developing severe CDI compared with those with a higher 25(OH)D status. No significant association was found between 25(OH)D status and CDI recurrence. Conclusion : The results of this meta-analysis suggest that lower mean concentrations of 25(OH)D were associated with CDI. A lower 25(OH)D status increased the odds of severe CDI but not of CDI recurrence.